(untitled) (Global Journal of Science Frontier Research, 2023)
People are increasingly confronted with starker choices in resource distribution to competing applications and users. At the local level, for example, land and water allocation for agricultural, industrial, municipal, recreational, and conservation operations is frequently a zerosum game. This is evidenced by the widespread loss of water and land from natural habitats to farms and, increasingly, to urban and industrial uses. From both an ethical and a practical standpoint, these choices are getting increasingly complex and difficult to reconcile. The Ecosystem Services Framework combines the biophysical and social aspects of environmental preservation in a way that has a lot of promise for dealing with the environmental catastrophe that will most certainly peak in the twenty-first century. A quick description of this framework was presented here, along with a suggestion for immediate action.